Oxidative stress predicts cognitive decline with aging in healthy adults: an observational study - Ihab Hajjar; Salim S. Hayek; Felicia C. Goldstein; Greg Martin; Dean P. Jones; Arshed Quyyumi (Journal of Neuroinflammation, 2018)
Abstract Background Redox signaling, which can be assessed by circulating aminothiols, reflects oxidative stress (OS) status and has been linked to clinical cardiovascular disease and its risk factors. These, in turn, are related to executive function decline. OS may precede the pro-inflammatory state seen in vascular disease. The objective of this study is to investigate the association between aminothiol markers of OS and inflammation in cognitive decline, especially in the executive cognitive domain which is highly susceptible to cardiovascular risk factors and is an important predictor of cognitive disability. Methods The study design is that of a longitudinal cohort study within the setting of a large academic institution with participants being university employees (n = 511), mean age 49 years, 68% women, and 23% African-American. These participants were followed for four consecutive years with a yearly cognitive assessment conducted using computerized versions of 15 cognitive tests. Peripheral cystine, glutathione, their disulfide derivatives, and C-reactive protein (CRP) were measured. Results Lower levels of glutathione at baseline was associated with a decline in the executive domain over 4 years (covariate-adjusted relative risk (RR) for glutathione = 1.70 (95% CI = 1.02–2.85), p = 0.04). Furthermore, a longitudinal decline in glutathione level was associated with a faster decline in the executive domain (p = 0.03). None of the other OS markers or CRP were linked to cognitive decline over 4 years. Conclusion Increased OS reflected by decreased glutathione was associated with a decline in executive function in a healthy population. In contrast, inflammation was not linked to cognitive decline. OS may be an earlier biomarker that precedes the inflammatory phase of executive decline with aging.